Photocatalytic Removal Of Phenol Using Titanium Dioxide (TiO2) In Fluidized Bed Reactor - Tan , Yong Nian (2012)

(untitled)
Fluorinated titanium dioxide (F-TiO2) and immobilized F-TiO2 were synthesized by sonication-hydrothermal method and binding method. Fluorine doping, immobilization, hydrothermal method and fluidized bed reactor used in this study. The samples were characterized by X-ray diffraction (XRD), Brunauer- Emmett-Teller (BET) analysis, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM). The photocatalytic degradation of phenol using the prepared photocatalyst was evaluated under UV light irradiation in batch mode fluidized bed reactor.